The influence of structural gradients in large pore organosilica materials on the capabilities for hosting cellular communities. Issue 29 (5th May 2020) - Bronner, Hannah; Holzer, Anna-Katharina; Finke, Alexander; Kunkel, Marius; Marx, Andreas; Leist, Marcel; Polarz, Sebastian
Abstract : Chemical and structural gradients in biofunctionalized organosilica–polymer nanocomposites control cell adhesion properties and open perspectives for artificial cellular community systems. Abstract : Cells exist in the so-called extracellular matrix (ECM) in their native state, and numerous future applications require reliable and potent ECM-mimics. A perspective, which goes beyond ECM emulation, is the design of a host-material with features which are not accessible in the biological portfolio. Such a feature would, for instance, be the creation of a structural or chemical gradient, and to explore how this special property influences the biological processes. First, we wanted to test if macroporous organosilica materials with appropriate surface modification can act as a host for the implementation of human cells like HeLa or LUHMES. It was possible to use a commercially available polymeric foam as a scaffold and coat it with a thiophenol-containing organosilica layer, followed by biofunctionalization with biotin using click chemistry and the subsequent coupling of streptavidin–fibronectin to it. More importantly, deformation of the scaffold allowed the generation of a permanent structural gradient. In this work, we show that the structural gradient has a tremendous influence on the capability of the described material for the accommodation of living cells. The introduction of a bi-directional gradient enabled the establishment of a cellular community comprising different cell types in spatially distinct regions of the material. An interesting perspective is to study communication between cell types or to create cellular communities, which can never exist in a natural environment.